Cell Sources and Influencing Factors of Liver Regeneration: A Review - Zhu, Chengzhan; Dong, Bingzi; Sun, Leqi; Wang, Yixiu; Chen, Shuhai (Medical science monitor, 2020)
Liver regeneration (LR) is a set of complicated mechanisms between cells and molecules in which the processes of initiation, maintenance, and termination of liver repair are regulated. Although LR has been studied extensively, there are still numerous challenges in gaining its full understanding. Cells for LR have a wide range of sources and the feature of plasticity, and regeneration patterns are not the same under different conditions. Many patients undergoing partial hepatectomy develop cirrhosis or steatosis. The changes of LR in these cases are not clear. Many types of cells participate in LR. Hepatocytes, biliary epithelial cells, hepatic progenitor cells, and human liver stem cells can serve as the cell sources for LR. However, different types and degrees of damage trigger the response from the most suitable cells. Exploring the cell sources of LR is of great significance for accelerating recovery of liver function under different pathological patterns and developing a cell therapy strategy to cope with the shortage of donors for liver transplantation. In clinical practice, the background of the liver influences regeneration. Fibrosis and steatosis create different LR microenvironments and signal molecule interaction patterns. In addition, factors such as partial hepatectomy, aging, platelets, nerves, hormones, bile acids, and gut microbiota are widely involved in this process. Understanding the influencing factors of LR has practical value for individualized treatment of patients with liver diseases. In this review, we have summarized recent studies and proposed our views. We discuss cell sources and the influential factors on LR to help in solving clinical problems.